1986
DOI: 10.3109/00016348609158396
|View full text |Cite
|
Sign up to set email alerts
|

Increased 2Nd Trimester Hemoglobin Concentration in Pregnancies Later Complicated by Hypertension and Growth Retardation: Early Evidence of a Reduced Plasma Volume

Abstract: Second-trimester hemoglobin (Hb) concentration was measured in 1535 pregnancies. Mean Hb concentration was significantly increased in women who developed pregnancy-induced hypertension (PIH) in the last trimester before the 37th week (p less than 0.01). A similar trend was also observed in nulliparous women who gave birth to infants with a birthweight below the 10th percentile, especially in smokers. The highest Hb concentrations were found in women with both PIH and intra-uterine growth retardation (IUGR). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 12 publications
6
47
1
1
Order By: Relevance
“…Information on the effect of smoking on Hb concentration or plasma volume changes in pregnancy is scarce. In agreement with our study, two other studies [8,9] report lower secondtrimester Hb levels in smokers than non-smokers. However, in these studies, Hb change was not a major issue or factors such as maternal age or weight gain were not controlled.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Information on the effect of smoking on Hb concentration or plasma volume changes in pregnancy is scarce. In agreement with our study, two other studies [8,9] report lower secondtrimester Hb levels in smokers than non-smokers. However, in these studies, Hb change was not a major issue or factors such as maternal age or weight gain were not controlled.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier studies have reported that, in non-pregnant women, smoking can cause polycythemia and thus increase the hemoglobin (Hb) concentration [7], whereas other studies have reported a tendency to decreased second-trimester Hb levels in smokers [8,9], probably indicating increased plasma volume expansion. However, as these studies did not control for factors such as maternal age and weight gain, the results are uncertain.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This idea is dismissed by observations of normal non-pregnancy plasma volume in women with complicated pregnancies 10 . There is also evidence that plasma volume fails to increase early in the second trimester before clinical onset of PE and FGR 8,35,59,[66][67][68] . There is a gap in available data concerning plasma volume values early in pregnancy in women developing PE or FGR later in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 On the other hand, it was argued that a high maternal haemoglobin (Hb) level from iron supplementation would reduce placental perfusion due to increase in blood viscosity and cause adverse pregnancy outcomes such as low birthweight, preterm births, pre-eclampsia and stillbirths. [4][5][6] This is further complicated by increasing concerns about the association between iron status and type II diabetes mellitus (DM). The frequency of diabetes in women with hereditary haemochromatosis, an inherited iron overload syndrome, provided the initial suggestion that systemic iron overload could contribute to abnormal glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%